Alkaloids – Bridging Natural Products in Antidiabetic Therapy (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
This review thoroughly assesses the antidiabetic properties of natural alkaloids, addressing their modes of action and treatment prospects for diabetes mellitus. Following PRISMA 2020 guidelines, literature from databases like PubMed/MEDLINE, Scopus, and Science Direct, published from 2000 to May 2025, was analyzed. The review highlights several promising alkaloids, including berberine, vindoline, harmine, trigonelline, oxymatrine, and solanine. These compounds have various anti-diabetic actions via improving insulin sensitivity, increasing insulin secretion, blocking digestive enzymes, modifying gut microbiota, and reducing oxidative stress and inflammation. For instance, berberine demonstrates efficacy comparable to standard hypoglycemics, partly through gut microbiota modulation. Harmine uniquely promotes pancreatic β-cell regeneration. Despite their therapeutic promise, significant challenges persist, including issues of bioavailability, varying toxicity profiles, and a notable scarcity of robust clinical trials. Standardization of plant sources and extraction methods also remains a critical challenge. Future research must prioritize rigorous clinical validation, advanced formulation development to enhance efficacy and safety, and strengthened regulatory frameworks. Alkaloids represent a promising frontier for developing novel, effective, and safe antidiabetic therapies.